Journalism and society - McQuail, Denis (SAGE, 2013)
"This is a major new statement on the role of journalism in democracy from one of media and communication?s leading thinkers. Denis McQuail leads the reader through a systematic exploration of how and why journalism and society have become so inextricably entwined and - as importantly - what this relationship should be like. It is a strong re-statement of the fundamental values that journalism aspires to." -- Publisher website.